Effect of Terramycin® and Bovatec® in free-choice mineral mixtures on gains of heifers grazing native grass - F. Brazle; Gerry L. Kuhl; D. Harmon; S. Laudert (Kansas Agricultural Experiment Station Research Reports, 1987)
Supplementing heifers in an intensive-early grazing program with Terramycin ® or Bovatec ® in free-choice, mineral-soybean meal mixtures resulted in Comparable cattle performance. Both feed additive mixtures increased heifer gains about .3 lb per day compared to controls supplemented with a simple mineral mixture.
Keywords: Cattlemen' s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Terramycin®; Bovatec®; Heifers; Mineral; Native grass